DO FRIENDSHIP ATTACHMENT AND POSITIVE AND NEGATIVE EMOTIONS ENCOURAGE PROSOCIAL BEHAVIOR AMONG ADOLESCENTS IN MALAYSIA? - Kadir, Nor Ba’yah Abdul (International Journal of Psychosocial Rehabilitation, 2020)
To investigate the associations between friendship attachment and positive and negative emotions on prosocial behavior in adolescents in Klang Valley, Malaysia. This is quantitative study. 429 adolescents between 13 to 22 years old, were selected to participate in this study using purposive sampling. The instruments used in this study were The Modified Differential Emotions Scale (mDES) for negative and positive emotions, The Adolescents Friendship Attachment Scale (AFAS) for friendship attachment, and prosocial behavior questionnaire that have been developed by authors. The results showed that there was a significant positive relationship between secure friendship attachment, negative and positive emotions on prosocial behavior. A significant negative relationship between anxious friendship attachment and avoidant friendship attachment on positive emotion were also found. The findings also found that three factors are needed to become a predictor of prosocial behavior. The research resulted in understanding the importance of friendship attachment and the effects of negative and positive emotions in enhancing understanding prosocial behavior among Malaysian adolescents. This study assists social workers and psychologists to design intervention programs in order to promote prosocial behavior and to build a secure friendship attachment among adolescents. The findings will also help the mental health professionals to classify adolescents’ emotions and behavior in school settings in order to correct their behavior difficulties and to stabilize their emotional instability using emotional and behavioral therapy.